2022
DOI: 10.3389/fpsyg.2022.925675
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Positive and Negative Information Processing in COVID-19 Vaccine Uptake in Women of Generation X, Y, and Z: The Power of Good is Stronger Than Bad in Youngsters?

Abstract: BackgroundPositive and negative focus in information processing associated with age has a diverse role in COVID-19 vaccine uptake. The aim of the study was the exploration of the generational diversity among psychological predictors of COVID-19 vaccine uptake.MethodsA cross-sectional research was conducted. The sample included 978 Hungarian women. Based on former literature findings, the COVID-19 vaccine uptake predictors were chosen from the health beliefs model, COVID-19 vaccine hesitancy, and psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…One of the cross-sectional surveys conducted in China reveals P-SUS, P-BAR and P-BEN to be the significant predictors of COVID-19 vaccine hesitancy, with higher levels of P-BAR being the most significant predictor [25]. Likewise, another study conducted in Hungary found that P-BAR significantly reduces the likelihood of COVID-19 vaccination uptake, whereas P-BEN increases the probability of vaccination uptake by four folds [26]. On the other hand, other studies also highlight the role of P-SEV and P-SUS to be significant predictors of COVID-19 vaccination uptake [27,28].…”
Section: Health Belief Modelmentioning
confidence: 99%
“…One of the cross-sectional surveys conducted in China reveals P-SUS, P-BAR and P-BEN to be the significant predictors of COVID-19 vaccine hesitancy, with higher levels of P-BAR being the most significant predictor [25]. Likewise, another study conducted in Hungary found that P-BAR significantly reduces the likelihood of COVID-19 vaccination uptake, whereas P-BEN increases the probability of vaccination uptake by four folds [26]. On the other hand, other studies also highlight the role of P-SEV and P-SUS to be significant predictors of COVID-19 vaccination uptake [27,28].…”
Section: Health Belief Modelmentioning
confidence: 99%